Assessment of the Impact of Agricultural Collaboration Practices on The Income of Farmers through Muzara'ah And Mukhabarah Contracts - Oktaviani, Tesya; Rahma, Tri Inda Fadhila; Harahap, Muhammad Ikhsan (Universitas Trunojoyo Madura, 2024)
This research aims to find out about income from muzara'ah and mukhabarah contracts.This research uses a qualitative approach with a descriptive method. Data collection using the participatory observation method for 1 month to see the profit-sharing system in agriculture, comparison of the Muzara'ah and Mukhabarah systems, potential and obstacles to the profit-sharing system. This research took 10 respondents. The subject of this study is muzara'ah and mukhabarah contracts and the object of this research is the agricultural interests of the Blang Mancung Village community in Aceh.Research results: Of the 10 farmers I interviewed, 6 people entered a muzara'ah contract, 2 people entered a mukhabarah agreement, and 2 people did not carry out muzara'ah or mukhabarah cooperation. Agricultural cooperation carried out by the community in Blang Mancung Village carries out muzara'ah and mukhabarah cooperation agreements based only on verbally because the community already trusts each other. An agreement like this is permissible according to Islamic law, this is based on the fiqh rule